Association of IRF5 (rs2004640), STAT4 (rs7574865), and TNFAIP3 (rs6920220, rs2230926) gene polymorphisms with primary Sjögren's syndrome and its complication, MALT-lymphoma - I. A. Guseva; A. V. Torgashina; J. I. Khvan; M. Yu. Krylov; E. Yu. Samarkina; N. V. Konovalova; D. A. Varlamov (Современная ревматология, 2023)
In recent years, more and more data have emerged confirming the contribution of non-HLA genetic markers to the predisposition to thedevelopment of Sjögren's syndrome (SS) and its severe complication, MALT-lymphoma.   Objective: to study the association of polymorphisms of IRF5 (rs2004640), STAT4 (rs7574865), and TNFAIP3 (rs6920220, rs2230926) genes with predisposition to the development of SS and MALT-lymphoma.   Materials and methods. The study included 80 patients with SS and 103 individuals in the control group. Sixteen patients were diagnosed with MALT-lymphoma. Genotyping of polymorphisms of IRF5 (rs2004640), STAT4 (rs7574865), TNFAIP3 (rs6920220, rs2230926) genes was performed by real-time polymerase chain reaction using original allele-specific probes labeled with different fluorescent labels.   Results and discussion. The distribution of genotypes and alleles of the STAT4 gene differed statistically significantly in the study and control groups of patients (p = 0.0005 and p = 0.0001, respectively). The presence of the homozygous TT genotype increased the risk of developing SS more than eightfold compared to TG+GG genotypes (odds ratio, OR=8.2; 95 % confidence interval, CI 2.5–30.0; p=0.0001)]. The polymorphism of the TNFAIP3 rs2230926 gene was also associated with the risk of developing SS: the presence of the TG genotype significantly increased the probability of developing SS compared to the TT genotype (OR 6.4; 95% CI 1.2–44.3; p = 0.01). The development of MALT-lymphoma was associated with the rs6920220 polymorphism of the TNFAIP3 gene. In 10 out of 16 patients with MALT-lymphoma (62.5 %) at least one minor A allele (AA+GA) was detected, while in patients without MALT-lymphoma only in 32.8 % of patients at least one minor A allele was detected (OR=3.4, CI 1.1–10.7; p=0.03). In addition, a correlation was found between the rs7574865 TT genotype of the STAT4 gene and the risk of developing severe leukopenia in SS, which was significantly more frequent in carriers of the TT genotype than in individuals with the GG + GT genotype (OR 4.9; 95 % CI 1.7–14.4; p = 0.004). Polymorphism of the IRF5 gene (rs2004640) was not associated with risk of developing SS or with clinical manifestations of the disease.   Conclusion. Polymorphisms rs7574865 of STAT4 gene, rs6920220, rs2230926 of TNFAIP3 gene are associated either with the risk of developing SS or with severe complications of the disease, MALT-lymphoma and leukopenia.